PERANAN TASAWWUF DALAM SOSIALISASI ISLAM DI INDONESIA - Masyhudi (Berkala Arkeologi, 2001)
Of the many literary works that tend to contain mystical teachings or tasawwuf, it shows that Islam and its Sufism have had an appeal among Muslim literati in the past. Not only because of its relevance to humans, but also because of its aesthetic view that is more satisfying, compared to the aesthetic view of Western humanists, because for Islam, the aesthetic view of beauty is a natural grace or gift from God. Beauty is a part of God's nature which has spiritual value and liberation from material life, so that in Islam, beauty is a proof of divinity. Thus it seems increasingly clear that in Indonesia, tasawwuf plays an important role in the socialization process of Islam.